The Retrospective Acceptability of High Intensity versus Low Intensity Speech Intervention in Children with a Cleft Palate: A Qualitative Study from the Parents' Point of View Using the Theoretical Framework of Acceptability - Alighieri, Cassandra; Van Lierde, Kristiane; Cammu, Heleen; Vanoost, Laure; Bettens, Kim (International journal of language & communication disorders, 2023)
Background: Increasing attention is paid to the effectiveness of high-intensity speech intervention in children with a cleft (lip and) palate (CP±L). It is, however, unknown if high-intensity intervention is acceptable to the intervention recipients. Parents have an integral role in supporting their children with intervention highlighting the importance of intervention acceptability to parents. Aims: To compare the retrospective acceptability of high-intensity speech intervention (10 1-hr speech therapy sessions divided over 2 weeks) with the retrospective acceptability of low-intensity speech intervention (10 1-hr speech therapy sessions divided over 10 weeks) for children with a CP±L from the parents' point of view. Methods & Procedures: Twelve parents of 12 children, aged 6-0 years who received high-intensity speech intervention (n = 6) or low-intensity speech intervention (n = 6), were invited to participate in this study. Seven parents (n = 3 in the high-intensity group and n = 4 in the low-intensity group) agreed to participate (total response rate: 7/12, 58.33%). A qualitative study design using semi-structured interviews was applied. To investigate the retrospective acceptability of the two intervention intensities, deductive coding according to the Theoretical Framework of Acceptability (TFA) was used. Outcomes & Results: With regard to the TFA construct 'affective attitude', results demonstrated that parents had positive feelings about the provided speech intervention regardless of the intensity. Parents of children who received high-intensity speech intervention reported two specific benefits related to the high intervention intensity: (1) it improved their relationship with the speech-language pathologist and (2) it improved their child's ability to make self-corrections in his/her speech. Even though both high-intensive and low-intensity speech intervention were considered burdensome (TFA construct 'burden'), parents were less likely to drop out of high-intensity intervention because the total intervention period was kept short. Conclusions & Implications: In conclusion, high-intensity speech intervention seemed acceptable to parents. More positive codes were identified for some of the TFA constructs in the high-intensity intervention group than in the low-intensity intervention group. Considering that some parents doubted their self-efficacy to participate in high-intensity speech intervention, speech-language pathologists need to counsel them so that they can adhere to the high intervention intensity. Future studies should investigate whether high-intensity speech intervention is also acceptable to the children who receive the intervention and to the speech-language pathologists who deliver the intervention.